Microleakage of five separated nickel-titanium rotary file systems in the apical portion of the root canal - Seyed Mohsen Hasheminia; Alireza Farhad; Hamidreza Davoudi; Dorna Sarfaraz (Wolters Kluwer Medknow Publications, 2022)
Background: The aim of this study was to evaluate the rate of apical microleakage following the fracture of five types of nickel-titanium rotary file systems (ProTaper Universal, Mtwo, RaCe, Revo-s, HeroShaper) in the apical one-third of the canal. Materials and Methods: In this laboratory experiment, 49 mandibular premolars were collected and randomly divided into seven groups. Root canal treatment was performed by five different rotary file systems with different cross-sections. All files, except in the control groups, were scratched at the 3-mm end by a handpiece. After separation of the apical end of the file in the root canal, the apical seal was measured, using the fluid infiltration technique. Data were analyzed in SPSS, using one-way ANOVA and Tamhane's T2 tests at P < 0.05. Results: The Hero Shaper and RaCe files showed the highest (3.14 μL/min) and the lowest (2.51 μL/min) rates of microleakage over time, respectively. There were significant differences between the Hero Shaper and RaCe files and between Hero Shaper and ProTaper files in terms of microleakage (Tamhane's T2 tests, P < 0.05) Conclusion: The presence of a separated file and its cross-section type affects the apical microleakage.